Microneedles-based local photothermal therapy promotes browning of white adipose tissue and combats obesity - Le Li; Hanxing Chen; Kexin Zhang; Xinying Hu; Mengfan Xu; Taotao Wen; Jialuo Ding; Mengyuan Zhao; Yeying Li; Yu Su; Zhenkun Lin (Materials Today Bio)
Obesity has emerged as a global epidemic, posing a significant threat to human health and imposing a huge burden on healthcare systems worldwide. White adipose tissue (WAT) browning has been recognized a promising therapeutic strategy to combat obesity and its associated metabolic disorders. Herein, Fe3O4 nanoparticles-encapsulated microneedles patch (Fe3O4@MNP)-based local photothermal therapy (LPTT) is developed with near-infrared (NIR) irradiation, aiming for a new approach to promote WAT browning in high-fat diet (HFD)-induced obesity. Our findings indicate that the Fe3O4@MNP possesses high mechanical strength and superior photothermal efficiency. Following four weeks of LPTT treatment (i.e. Fe3O4@MNP + NIR), the significant therapeutic efficacy of anti-obesity in obese mice is achieved with high biosafety, amounting to a 19 % decrease in body weight compared to the HFD group. Meanwhile, LPTT treatment exhibits significant effectiveness in restraining fat expansion, improving glucose tolerance and lipid metabolism, and alleviating nonalcoholic fatty liver disease (NAFLD). Especially, LPTT treatment promotes WAT browning and thermogenesis, that mediated through the activation of the HSF1-PGC1α transcriptional axis and upregulation of HSP72. This work demonstrates that microneedles-based LPTT can effectively promote WAT browning with excellent effectiveness and high biosafety, presenting a new therapeutic platform for the treatment of obesity and related metabolic disorders.